HUBUNGAN AKTIVITAS FISIK DENGAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS DI WILAYAH RW 003 KELURAHAN GANDARIA UTARA - Lisa Septiani (2020)
Diabetes mellitus is a metabolic disorder characterized by high blood glucose levels. Complications for the disease can be prevented by taking four main actions namely education, diet, physical activity, and pharmacological intervention. Physical activity is a body movement performed by the muscles and their supporting systems to release energy. Good physical activity can help the pancreas break down glucose into the cell if insulin is not produced, so in diabetic this physical activity is essential for blood glucose levels in diabetic patients to be reduced or normal.This study was conducted to analyze the relationship of physical activity to blood glucose levels in diabetic patients with diabetes mellitus in RW 003 North Gandaria District. This study used Chi-Square test with Cross Sectional design conducted on 82 respondents by total sampling method. Collecting data in this study using a questionnaire with 3 parts, namely the first part to fill demographic data, fill in the physical activity questionnaire that has been tested for validity and reliability, fill in the informed consent, then the respondent is willing to check blood sugar at any time. Statistical test results showed p value = 0,000 which means that there is a significant relationship between physical activity and blood glucose levels in patients with diabetes